Farmers' participatory alternate wetting and drying irrigation method reduces greenhouse gas emission and improves water productivity and paddy yield in Bangladesh - Hossain, Mohammad Mobarak; Islam, Mohammad Rafiqul (MDPI, 2022)
In dry season paddy farming, the alternate wetting and drying (AWD) irrigation has the potential to improve water productivity and paddy production and decrease greenhouse gas (GHG), such as methane (CH4) and nitrous oxide (N2O), emissions when compared to continuous flooding (CF). Participatory on-farm trials were conducted from November 2017 to April 2018 in the Feni and Chattogram districts of Bangladesh. Total 62 farmers at Feni and 43 at Chattogram district, each location has 10 hectares of land involved in this study. We compared irrigation water and cost reductions, paddy yield, and CH4 and N2O emissions from paddy fields irrigated under AWD and CF irrigation methods. The mean results of randomly selected 30 farmers from each location showed that relative to the CF irrigation method, the AWD method reduced seasonal CH4 emissions by 47% per hectare and CH4 emission factor by 88% per hectare per day. Moreover, the AWD decreased the overall global warming potential and the intensity of GHG by 41%. At the same time, no noticeable difference in N2O emission between the two methods was observed. On the other hand, AWD method increased paddy productivity by 3% while reducing irrigation water consumption by 27% and associated costs by 24%. Ultimately it improved water productivity by 32% over the CF method.